2001
DOI: 10.1542/peds.108.5.e96
|View full text |Cite
|
Sign up to set email alerts
|

Unmasking of Childhood Hypothyroidism by Disseminated Xanthomas

Abstract: ABSTRACT. Secondary hyperlipidemia is a common laboratory finding in children with nephrotic syndrome, diabetes mellitus, and hypothyroidism. However, clinical signs of hyperlipidemia are extremely rare in childhood.We report on an 11-year-old girl who presented with a disseminated yellow papulomatous rash on the lower limbs and yellow skin creases on the palms of her hands. Blood tests yielded an opaque serum with a triglyceride concentration of 820 mg/dL and cholesterol of 1050 mg/ dL. Skin biopsy of one of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
1
0
3
Order By: Relevance
“…Because retinoic acid treatment decreases TR expression in a dose-dependent manner (41) and chronic alcohol intake results in lower levels of hepatic vitamin A and retinoic acid (Table 1), we proposed that alcohol treatment could indirectly increase hepatic TR expression by decreasing vitamin A levels in the livers. In addition, it has been reported that patients with hypothyroidism accumulated significant amounts of carotenoids in their body (41,44) and that CMO1 was upregulated by T 3 (17). Therefore, we speculate that the increase in TRb could augment thyroid hormone's effects and contribute to the upregulation of CMO1.…”
Section: Discussionmentioning
confidence: 77%
“…Because retinoic acid treatment decreases TR expression in a dose-dependent manner (41) and chronic alcohol intake results in lower levels of hepatic vitamin A and retinoic acid (Table 1), we proposed that alcohol treatment could indirectly increase hepatic TR expression by decreasing vitamin A levels in the livers. In addition, it has been reported that patients with hypothyroidism accumulated significant amounts of carotenoids in their body (41,44) and that CMO1 was upregulated by T 3 (17). Therefore, we speculate that the increase in TRb could augment thyroid hormone's effects and contribute to the upregulation of CMO1.…”
Section: Discussionmentioning
confidence: 77%
“…Die Hälfte unserer PatientInnen wies mäßiggradig erhöhte Serumcholesterinwerte bis zu 300 mg/dl auf. Auch das gemeinsame Auftreten von XP und Schilddrüsen‐Funktionsstörungen wurde schon beschrieben und zwar sowohl bei Individuen mit Hyperthyreoidismus [4] als auch solchen mit Hypothyreoidismus [5]. Weitere Untersuchungen werden zeigen, ob es sich dabei um eine Kausalität handelt oder nicht, in unserem Kollektiv fanden sich jedenfalls 21,4 % der Xp‐Betroffenen in Therapie einer hypothyreoten Stoffwechsellage.…”
Section: Diskussionunclassified
“…Weitere Untersuchungen werden zeigen, ob es sich dabei um eine Kausalität handelt oder nicht, in unserem Kollektiv fanden sich jedenfalls 21,4 % der Xp‐Betroffenen in Therapie einer hypothyreoten Stoffwechsellage. Den möglichen Zusammenhang von Xp und Diabetes mellitus konnten wir nicht bekräftigen [4, 5].…”
Section: Diskussionunclassified
See 1 more Smart Citation